THE INFLUENCE OF COLLABORATIVE-CONSTRUCTIVIST LEARNING MODEL OF STUDENT’S SCIENCE PROCESS SKILL AT SMA NEGERI 2 KARANGANYAR IN ACADEMIC YEAR 2012/2013 - -, Mutia Dwi Z, Baskoro Adi P, Harlita (P Biologi FKIP UNS Surakarta, 2015)
Learning biology as part of the science consists of three aspects, namely the process (psychomotor), product (cognitive), and scientific attitudes (affective). In reality the classrooms are not conducive for the learning process is dominated by teachers and more advanced aspects of the product rather than process aspects and scientific attitude. consequently students are less oriented to the development of science process skills. Learning model that can facilitate the students to develop science process skills are collaborative-constructivist learning model. Both have characters that complement each other. The aim of this research is to ascertain the influence of collaborative- constructivist learning model of student?s Science Process skill at SMA Negeri 2 Karanganyar in academic year 2012/2013. This research was quasi experiment research which used posttest only nonequivalent control group design.The population of this research was all of X grade students at SMA Negeri 2 Karanganyar in academic year 2012/2013. Sampling techniques used cluster sampling that choosed X5 as experiment group and X8 as control group. Data was collected using test and non test. Test method using science process skill test. Non test method using observation sheet and document. The hypotheses analyzed by t-test. This research concluded that application of collaborative- constructivist learning model has real influential toward science process skill of students at SMA Negeri 2 Karanganyar. Key Words: Collaborative-Constructivist Learning Model, Science Process Skill